Effect of Waxy Corn Starch on the Quality of Dumpling Wrappers - WANG Yuan, LOU Haiwei, ZHAO Renyong (Shipin Kexue, 2023)
In order to explore the effect of waxy corn starch on the quality of dumpling wrappers, the effects of adding different amounts of waxy corn starch on the color, toughness, freezable water content and microstructure of dumpling wrappers and the cooking quality of unfrozen and frozen dumpling wrappers were investigated. The results showed that waxy corn starch addition could significantly improve the brightness (L*) value, toughness and starch binding capacity, and reduce the content of freezable water in dumpling wrappers. Moreover, waxy corn starch addition significantly shortened the cooking time, reduced the cooking loss, increased the shear hardness, and improved the sensory quality of frozen dumpling wrappers. The transparency, cooking loss, shear hardness and chewiness of frozen dumpling wrappers were better than those of unfrozen dumpling wrappers. In summary, the quality of frozen dumpling wrappers can be improved by adding 4%–6% waxy corn starch, which provides a theoretical basis for the development of waxy corn starch in the food industry.